Heart of culture - Steyn, Selwyn (School of Architecture, Planning and Geomatics, 2023)
If the urban landscape is the body politic made inertly manifest, then cultural and civil space acts as the heart. Cultural space allows for the societal corpus to gaze into itself. Cultural space however is commonly made to act as gilded cages -held aloft within ivory towers- with a negation of its civic value. A cultural heart, an institutional anchor, tying the past and future is most prescient within the context of Cape Town's Foreshore, simultaneously addressing the complex urban needs of an unstitched Modernist landscape and anticipating rapid developmental flux that will see the city change explosively. This dissertation scheme aims to reinterpret the art museum typology which typically generates an insular and monastic aesthetic experience in which one is removed fully from the world. Here rather, the program questions how public functions and museum functions can be interspersed and dynamically overlayed so that maximal conversation and cross pollination may occur with public life influencing the experience of art.